2020
DOI: 10.1590/1984-0462/2020/38/2019016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insulin Resistance and Association With Metabolic Risk Factors and Food Consumption in Adolescents - Recife/Brazil

Abstract: Objective: To identify the prevalence of insulin resistance in adolescents and its associations with metabolic factors and food intake. Methods: Cross-sectional study conducted with a stratified, complex, school-based sample. The subjects were adolescents (n=1,081) who participated in the Study of Cardiovascular Risk in Adolescents in the city of Recife (Pernambuco, Brazil). We analyzed demographic, socioeconomic, behavioral, anthropometric, biochemical, and dietary variables. Insulin resistance was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
2
6
0
1
Order By: Relevance
“…Indeed, specific characteristics in each study, such as the age of the adolescent population and criteria used to define IR at each age may have influenced on this variation [ 31 ]. Similar to our findings, one study with Brazilian female adolescents using the 75th percentile of the HOMA-IR found a 27.8% prevalence of IR [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, specific characteristics in each study, such as the age of the adolescent population and criteria used to define IR at each age may have influenced on this variation [ 31 ]. Similar to our findings, one study with Brazilian female adolescents using the 75th percentile of the HOMA-IR found a 27.8% prevalence of IR [ 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…While the relationship between puberty and IR has been reported in different studies, IR and time of menarche have been addressed less frequently [ 9 ], although emerging evidence suggests an association between excess weight and age at menarche [ 10 , 11 ]. According to studies conducted in Brazil, it differs from other countries in being such a large country, with significant demographic, cultural and ethnic diversity among its regions, such as in the north and south of the country [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a large cohort of adolescents (with subjects included independently of their BMI), an energy-dense, high-fat, and low-fiber dietary pattern was positively associated with higher levels of insulin and HOMA-IR [ 51 ]. Moreover, a recent Brazilian cross-sectional study found that in a cohort of adolescents (again, including subjects independently of their BMI), an elevated saturated fat intake was associated with insulin resistance [ 52 ]. In adults, different studies on large cohorts and with long follow-up have demonstrated that a low-fat (but high-carbohydrate) diet is effective in the prevention of type 2 diabetes mellitus, reporting reductions in its incidence of up to 58% [ 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, verificou-se elevação nos níveis de insulina e HOMA-IR. Andrade et al 26 sugerem, no entanto, que a RI pode estar relacionada ao desenvolvimento na adolescência, envolvendo alterações hormonais e de composição corporal em indivíduos de estágios iniciais da puberdade, podendo ser revertida após o estirão de crescimento. No entanto, isso não explica os resultados encontrados, pois a maior parte da população estudada encontrava-se na fase final da puberdade.…”
Section: Lima Et Al Hipertensão E Fatores Associados Em Adolescentesunclassified